From crisis to war: prophetic dualism in President George W. Bush's September 20, 2001 address - Potucek, Rachel Eryn (Kansas State University, 2012)
President George W. Bush's September 20, 2001 televised address to a Joint Session of Congress stands in history as his Administration's first deliberate official rhetorical response to the events of 9/11 and the first instance of the "Bush Doctrine." Although 9/11 has become an increasing topic of scholarly review and this speech is the first presidential policy response, few have explored Bush's choice of metaphors in this speech. Metaphors are a powerful tool of rhetoric, especially in political rhetoric, because metaphors are uniquely adept at simplifying complex topics, and a study of metaphor can reveal a speaker's underlying worldview and beliefs. Through metaphorical analysis, this study identifies nine clusters of metaphor in Bush's September 20, 2001 address: FORCE/WAR, BODY, FEAR, LIGHT/DARK, NEAR/FAR, UNITY, FAITH/FATE, GOOD/EVIL and SAVAGE. This study contrasts metaphor clusters to "prophetic dualism," a worldview that defines foreign policy within the context of a specific set of moral beliefs, and concludes that the artifact meets all tenets of prophetic dualism as well as the core characteristics of presidential crisis rhetoric and civil religion (although the artifact does not meet all characteristics of presidential war rhetoric). The study closes with a discussion of practical, rhetorical and methodological implications that may be useful to scholars of rhetoric and political science, including suggestions for future research of prophetic dualism and presidential war rhetoric.
Keywords: Speech Communication; George W. Bush; Communication (0459)